Contralateral Axillary Metastasis in Breast Cancer : case report - Jalal Wrmzyar , Samya (Diyala Journal of Medicine, 2020)
Background:Contralateral axillary metastasis is a rare presentation in breast cancer, normally treated as a systemic disease. New researches shows that it may represent a locally advanced disease due to altered lymphatic drainage or it may be the only presentation of a contralateral primary occult breast cancer . Many recent publications have proposed aggressive surgical treatment with benefits to the patients in terms of survival. Case report: We present a case with a history of unilateral breast cancer, presented with contralateral axillary metastasis without any evidence of distant metastasis or new primary contralateral breast cancer. Conclusion: There is limited evidence of the correct management of contralateral axillary metastasis, and individualized multidisciplinary management is the best option for these patients , and it is proposed to be treat it as a loco regional disease for best survival benefit of the patient.